SISTEM INFORMASI AKADEMIK BERBASIS LARAVEL UNTUK REGISTRASI ULANG DAN PENGAJUAN CUTI MAHASISWA - Abdullah Ardi; Andriani (Universitas Majalengka, 2023)
Hasnur Polytechnic is a private educational institution located in Barito Kuala Regency. Currently Hasnur Polytechnic already has an information system that is intended to improve operational service activities such as HR Systems, Academic Systems, Payroll Systems, Internship Systems, Web Profile Systems. However, in this case, it is necessary to improve the quality of academic services in terms of re-registration and application for student leave, which was implemented before the existence of the system required a lot of time because management was carried out in an unsystematic manner. In designing this system, the Waterfall method is applied, starting from the communication stage to the construction stage. As for the process of communication stages of collecting the required data, it is requested directly from the relevant parties, namely the Academic Administration Section of the Hasnur Polytechnic. In the system design stage described using DFD. At the construction stage the system is carried out using the Laravel framework, and applying programming languages (PHP, HTML, JavaScript, and MySql Queries). In the final stage in the system aspect using Blackbox Testing, with 100% successful test results according to the design of functional requirements and running according to its function.